Qualification of a vertical cryostat for MLI performances tests between 20 K and 60 K to 4.2 K. (April 2019) - Venturi, V; Koettig, T; Chorowski, M; Polinski, J; Parma, V; Kopczynski, A
Abstract: Boil-off calorimetric measurements of Multilayer Insulation (MLI) performance from 20 K-60 K to 4.2 K are being performed at CERN, extending the range of measurements of MLI to cover cryostat applications where thermal shields are operated at lower temperatures than that of LN2. Possible applications include future large accelerators like the Future Circular Collider (FCC). The tests are carried out in an existing vertical test cryostat shielded with a liquid nitrogen cooled vessel and with an inner cylindrical liquid helium tank carrying the wrapped MLI sample. The cryostat has been modified to insert an additional intermediate thermal shield maintained at controlled temperatures in the 20 K-60 K range, by means of regulated power input from an electrical heater. This paper describes the test cryostat and the MLI performance measurement methodology as well as experimental results of the commissioning and calibration of the instrument.